2016
DOI: 10.3389/fnins.2016.00432
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biphasic Stimulation on Olfactory Ensheathing Cells for Neuroprosthetic Devices

Abstract: The recent success of olfactory ensheathing cell (OEC) assisted regeneration of injured spinal cord has seen a rising interest in the use of these cells in tissue-engineered systems. Previously shown to support neural cell growth through glial scar tissue, OECs have the potential to assist neural network formation in living electrode systems to produce superior neuroprosthetic electrode surfaces. The following study sought to understand the influence of biphasic electrical stimulation (ES), inherent to bionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…, living tissue), which can vary from system to system. 45,46,48 However, in this paper and for ease of discussion, the definitions of lower (0.1 to 0.75 mA) and higher currents (1 and 2.5 mA) will be used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, living tissue), which can vary from system to system. 45,46,48 However, in this paper and for ease of discussion, the definitions of lower (0.1 to 0.75 mA) and higher currents (1 and 2.5 mA) will be used.…”
Section: Resultsmentioning
confidence: 99%
“…16 However, there are no standard values regarding the voltage threshold of water electrolysis since these values are influenced by various system components, such as the counterelectrode and working electrode compositions. For example, in the literature, voltage magnitudes of 800 mV 45,46 and 600 mV 16 vs. a reference electrode Ag|AgCl have been reported as the voltage threshold for water electrolysis. Two-electrode setup CV was used here since this is the electrode configuration used for the PC12s ES.…”
Section: Morphological and Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of the hydrogel component, CHs swell in aqueous environments, enabling ingress of ions and forming a three dimensional surface through which charge is transduced. The substantially higher charge transfer area introduced by the CH enables coated electrodes to inject greater amounts of charge at lower voltage than their uncoated metallic counterparts and hence enable devices with low power consumption (Kim et al, 2004 ; Sekine et al, 2010 ; Pan et al, 2012 ; Hassarati et al, 2014 , 2016 ). In prior studies by Hassarati et al ( 2014 ) it was shown that CH coatings on cochlear implants imparted a reduction in potential transient of over 50% and maintained more stable electrical properties over a simulated 2 years of activity (two billion stimuli delivered continuously over 3 months in artificial perilymph).…”
Section: Introductionmentioning
confidence: 99%
“…These emerging studies are also applicable to OEC transplantation protocols. It has been proven that OECs can support neuronal differentiation and secrete neurotrophic factors under bipolar electrical stimulation of conductive hydrogel electrodes (Hassarati et al., 2016). Michael et al.…”
Section: Oec‐based Comprehensive Therapymentioning
confidence: 99%